Loan Loss Provisioning and Profitability of the Private Commercial Banks of Bangladesh - Sultana, Afrin; Jalloh, Talatu (International Journal of Economics and Financial Issues, 2025)
Loan Loss Provisioning is a major regulatory requirement for banks to maintain the stability of financial performance. In Bangladesh, non-performing loans (NPLs), are considered as the biggest challenge of the banking sector. Thus, loan loss provisioning has been an obligatory as well as financial risk management tool for the banks. This study aims to find out the impact of loan loss provisioning on the banks’ profitability measured in terms of ROA and ROE. The study covers twenty private commercial banks operating in Bangladesh. The study concentrated the bank specific variables such as bank size, the proportion of total loans and advances disbursed of total assets, current liabilities to total assets, total deposits to total assets. Besides, the control variables include the governance index and the inflation level. The findings demonstrate loan loss provision has significant impact on the banks’ profitability in Bangladesh.